2016
DOI: 10.1038/srep26942
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia-associated gene variations and expression patterns revealed by whole-genome and transcriptome sequencing of rabbit models

Abstract: The rabbit (Oryctolagus cuniculus) is an important experimental animal for studying human diseases, such as hypercholesterolemia and atherosclerosis. Despite this, genetic information and RNA expression profiling of laboratory rabbits are lacking. Here, we characterized the whole-genome variants of three breeds of the most popular experimental rabbits, New Zealand White (NZW), Japanese White (JW) and Watanabe heritable hyperlipidemic (WHHL) rabbits. Although the genetic diversity of WHHL rabbits was relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…In the previous study, we identified the gene mutations or modifiers through whole-genomic sequencing and deep transcriptome sequencing of LDL receptor deficient (WHHL) rabbits and cholesterol-fed New Zealand White rabbits. The previous study mainly addressed transcriptional changes in the WHHL rabbits, while cholesterol-fed New Zealand White rabbits were used as a reference 30 . To further emphasize the relationship with lipoprotein profiles and aortic atherosclerosis, in the current study, we focused on the hepatic gene expression changes and liver pathology in the setting of hepatic steatosis induced by cholesterol diet in the Japanese White rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, we identified the gene mutations or modifiers through whole-genomic sequencing and deep transcriptome sequencing of LDL receptor deficient (WHHL) rabbits and cholesterol-fed New Zealand White rabbits. The previous study mainly addressed transcriptional changes in the WHHL rabbits, while cholesterol-fed New Zealand White rabbits were used as a reference 30 . To further emphasize the relationship with lipoprotein profiles and aortic atherosclerosis, in the current study, we focused on the hepatic gene expression changes and liver pathology in the setting of hepatic steatosis induced by cholesterol diet in the Japanese White rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, the whole genome of WHHLMI rabbits was analyzed and compared with those of Japanese white rabbits and New Zealand white rabbits 72) . Although the authors described "genome information of WHHL rabbits" in the paper, they used "WHHLMI rabbits" in their study.…”
Section: Genome Analyses Of Whhlmi Rabbits and Identification Of Serumentioning
confidence: 99%
“…For a long time, generation of knock-out rabbits has been a dream for researchers because rabbit embryonic stem (ES) cells are not available and genomic information for rabbits is lacking. Rabbit genome sequencing was initially completed by a European group 26 ) , and two years later, we along with Chinese and US groups, successfully sequenced three rabbit genomes (New Zealand White, Japanese White and Watanabe heritable hyperlipidemic rabbits) and completed transcriptomic profiling of atherosclerotic lesions and the liver for these rabbits 27 ) . These genomic and RNA seq data will provide many insights into understanding the pathogenesis of atherosclerosis in rabbits.…”
Section: Knock-out Rabbitsmentioning
confidence: 99%